2015
DOI: 10.3391/mbi.2015.6.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Concepts for biocontrol in marine environments: is there a way forward?

Abstract: The occurrence of problematic pest organisms is an increasing global phenomenon, adversely affecting a range of environments and associated values. In marine systems, the efficacy of pest control has to date been constrained by a lack of tools that are not only highly effective, but also applicable across broad spatial scales. Here we consider the extent to which biological control (biocontrol) has the potential to fulfil these needs. We describe different biocontrol approaches and potential ecological mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(20 citation statements)
references
References 79 publications
1
18
0
1
Order By: Relevance
“…Mouse and clinical data have shown an increase in the abundance of this species after RYGB (Liou et al, 2013; Palleja et al, 2016), and here we observed a similar trend on SG patients. Faecalibacterium prausnitzii , a key species in the gut microbiome (Miquel et al, 2015), appeared under-represented post RYGB (Palleja et al, 2016). Sequencing data in this study also revealed other signature species with interesting changes.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse and clinical data have shown an increase in the abundance of this species after RYGB (Liou et al, 2013; Palleja et al, 2016), and here we observed a similar trend on SG patients. Faecalibacterium prausnitzii , a key species in the gut microbiome (Miquel et al, 2015), appeared under-represented post RYGB (Palleja et al, 2016). Sequencing data in this study also revealed other signature species with interesting changes.…”
Section: Discussionmentioning
confidence: 99%
“…This method of control of non-indigenous species is relatively well established in terrestrial and freshwater aquatic systems (e.g., Newman et al 1996, Baars et al 2010, Mangan & Baars 2013. Despite the promising preliminary results to date, this field is very much in its infancy in the marine environment (but see Atalah et al 2013aAtalah et al ,b, 2014Atalah et al , 2015, and further research is needed in this area.…”
Section: Removal Of Non-indigenous Speciesmentioning
confidence: 99%
“…Recently there has been a move towards biological control through the introduction of natural predators (e.g. Atalah et al 2014Atalah et al , 2015; or through the development of diverse and resilient communities-sensu the diversity resistance hypothesis (Elton 1958, Stachowicz et al 2002, Arenas et al 2006. Rare taxa are typically missing from artificial structures (Chapman 2003, Pister 2009).…”
Section: Discussionmentioning
confidence: 99%